THE GROWING ROLE OF DIGITAL INFORMATION TECHNOLOGY IN MODERN LIFE - Abdubannoyeva Adolatxon Aʼzamjon qizi; Mannobov Abdumalik Mansurjon oʿgʿli (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article, written from the perspective of a 6th grade student from Uzbekistan, examines the rapid rise of digital information technology and its far-reaching impact on modern society. It explores how technologies such as artificial intelligence, cloud computing, social media, and online education are transforming communication, learning, and business. The article also addresses the challenges that accompany digital progress — including cybercrime, privacy concerns, and internet addiction  —  and  calls  on  individuals,  especially  young  people,  to  engage  with technology in a responsible and informed manner.